The Situation Of Digital Teaching As A Strategic For Universiti’s Pedagogia Teaching - maatoug, fadila; toumi, tayeb (El Omda in Linguistics and Discourse Analysis, 2024)
In light of the twenty – first century , the world iswitnessing a massive technological revolutions.Among the most prominent of these tehnologicalchanges , wefindgreatprogress in the fields of communication and information exchange . In light of the new circumstances, it has becomenecessary for the educational institution to adopt modern methodsthat are compatible with the digital technologicaldevelopmentsthatwe have witnessed. Schools must integrate digital means as an essential and necessary part to improve the educationalprocess.Theyshouldalsoadopt digital learning tobe in touchwith the desirededucationalprocess. Therequirededucational goals are achieved.